2013
DOI: 10.1002/masy.201300038
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Thermal Gradient Interaction Chromatography and Crystallization Techniques for Composition Analysis in Polyolefins

Abstract: Summary Since the introduction of high temperature interaction chromatography for the analysis of polyolefins the technique has demanded a particular interest in the analysis of elastomers where crystallization techniques will meet a limitation given the low crystallinity of these polymers. In this paper the introduction of non carbon adsorption supports such as molybdenum sulfide, boron nitride and tungsten sulfide with equivalent separation to graphitized carbon packing in TGIC analysis of polyolefins is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 17 publications
3
62
0
Order By: Relevance
“…A nearly symmetric peak confirms that all polymers were unimodal in composition. As observed by Soares, Cong, and Monrabal copolymers elute in the order of decreasing hexene content . The elution temperature of the nine copolymers were plotted against hexene mol% (see the inset in Figure ).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…A nearly symmetric peak confirms that all polymers were unimodal in composition. As observed by Soares, Cong, and Monrabal copolymers elute in the order of decreasing hexene content . The elution temperature of the nine copolymers were plotted against hexene mol% (see the inset in Figure ).…”
Section: Resultsmentioning
confidence: 74%
“…Monrabal and co‐workers showed that any packing material having atomically flat surface provided the same separation as graphitic column. They suggested that the adsorption strength depends on the available surface area of the molecule (i.e., the length of the ethylene segments) in contact with the flat support surface . The adsorption is based on weak van der Waals forces interaction between nonpolar polyolefin and an atomic level flat surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prabhu et al / J. Chromatogr. A xxx (2015) xxx-xxx in SEC of ethylene/1-alkene copolymers [14,64,[98][99][100]. Only a few IR-transparent solvents (C-H absorbance) exist: TCB, ODCB, TCE and 1-chloronapthalene.…”
Section: Influence Of the Sec Separation And Use Of Ir Detection In 2mentioning
confidence: 99%
“…Moreover, they combined TGIC and CEF to form a cross‐fractionation instrument with enhanced peak separation. They also reported that other support types, such as molybdenum sulfide, boron nitride and tungsten sulfide, could also be used to fractionate polyolefins by HT‐TGIC …”
Section: Introductionmentioning
confidence: 99%